Budidaya Tanaman Kelor (Moringa Oleifera L) di Masyarakat Wolio - Wa Ode Sifatu; Hasniah Hasniah; Hartini Hartini; Israwati Israwati; Wa Ode Winesty Sofyani (Program Studi Agribisnis, Fakultas Pertanian, Universitas Singaperbangsa Karawang, 2022)
The purpose of this study is to find out the cultivation of moringa plants (Moringa oleifera Lam.) according to the views of the Wolio society. This research was conducted in Baubau, Southeast Sulawesi Province because Wolio society are culturally and hereditary supporters of moringa plants. To collect data used ethnographic methods, by combining techniques: observation participation (observation participation), and in-depth interviews (in-depth interview). The results showed that the cultivation of Moringa plants in the Wolio society is still carried out traditionally based on local knowledge of the society. Moringa cultivation in this area is an effort to align nature with plants that can be productive and adaptive in various places throughout the season. Cultivating moringa plants is a wise decision that benefits the society of Wolio since then and now, also shows the existence of local wisdom, among others, in terms of: land selection, seed selection, harvest techniques, post-harvest, and others.